2006
DOI: 10.1111/j.1365-2826.2006.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin‐1 Dose‐Dependently Modulates Maternal Behaviour in Mice

Abstract: Increases in neuronal activity of hypocretin (HCRT), a peptide involved in arousal, and in HCRT-1 receptor mRNA expression have recently been identified in association with lactation. HCRT is released within brain regions regulating maternal behaviour and it is possible that increased HCRT neurotransmission during lactation supports maternal care. The present study examined for the first time the behavioural effects of HCRT on lactating mice. At intermediate doses, intracerebroventricular (i.c.v.) injections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…Gene expression of OX is increased in pregnant and lactating female rats compared to nonpregnant or nonlactating rats (Kanenishi et al, 2004; Sun, Narita, Murata, Honda, & Higuchi, 2003), and the number of OX-expressing neurons is also increased during lactation (Sun et al, 2003). In accord with this, injection of OX-A into the cerebral ventricles or medial preoptic area specifically increases licking and grooming of pups but not of the self, while peripheral or medial preoptic area injections of an OX1R antagonist reduces these behaviors (D’Anna & Gammie, 2006; Rivas, Torterolo, Ferreira, & Benedetto, 2016). It is possible that the increase in OX during the perinatal period also contributes to other behaviors observed in mothers during this time, including disturbed sleep (Bei, Coo, & Trinder, 2015) and increased caloric intake (Whichelow, 1975), which are ultimately tied to care of the offspring.…”
Section: Role Of Orexin/hypocretin In Homeostatic Feeding and Othementioning
confidence: 65%
“…Gene expression of OX is increased in pregnant and lactating female rats compared to nonpregnant or nonlactating rats (Kanenishi et al, 2004; Sun, Narita, Murata, Honda, & Higuchi, 2003), and the number of OX-expressing neurons is also increased during lactation (Sun et al, 2003). In accord with this, injection of OX-A into the cerebral ventricles or medial preoptic area specifically increases licking and grooming of pups but not of the self, while peripheral or medial preoptic area injections of an OX1R antagonist reduces these behaviors (D’Anna & Gammie, 2006; Rivas, Torterolo, Ferreira, & Benedetto, 2016). It is possible that the increase in OX during the perinatal period also contributes to other behaviors observed in mothers during this time, including disturbed sleep (Bei, Coo, & Trinder, 2015) and increased caloric intake (Whichelow, 1975), which are ultimately tied to care of the offspring.…”
Section: Role Of Orexin/hypocretin In Homeostatic Feeding and Othementioning
confidence: 65%
“…Strikingly, Hcrt can increase locomotor activity independent of normal circadian oscillations in locomotor activity, and these oscillations dampen the effects of Hcrt overexpression. Because our experiments were performed on larvae, the results are not confounded by previous experience, feeding, thermoregulation, social interactions, or other complex homeostatic processes or behaviors in which Hcrt has been implicated in mammals (Sakurai et al, 1998;Szekely et al, 2002;Yamanaka et al, 2003;Harris et al, 2005;Borgland et al, 2006;D'Anna and Gammie, 2006). Our experiments therefore clarify the primary function of Hcrt and suggest that the most basal and ancestral role of Hcrt signaling is the promotion of wakefulness.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have found that isoflurane can depress c-Fos in the spinal cord (Jinks et al, 2002), but elevate it in the hypothalamus in aged rats (Jansson et al, 2004), so it is not clear how isoflurane may have acted in this study, if at all on c-Fos expression. As indicated above, the use of isoflurane in association with injection here was aimed to reduce stress effects of injection and its previous use in association with injection has not been found not to overtly impair aggression or other maternal behaviors (D'Anna et al, 2005;D'Anna and Gammie, 2006;Gammie et al, 2004). Exactly whether or how CDP and isoflurane may interact at the doses used in this study would need to be examined in subsequent experiments.…”
Section: Discussionmentioning
confidence: 97%
“…or i.p.) 30 min prior to testing does not impair production of maternal aggression or other maternal behaviors ( D'Anna et al, 2005;D'Anna and Gammie, 2006;Gammie et al, 2004). Immediately after injection, each mouse was placed back in the homeroom for 30 min prior to behavioral testing.…”
Section: Pharmacological Treatment and Injectionmentioning
confidence: 99%